Analisis Permendikbud Ristek No 30 Tahun 2021 dan Konstruksi Sosial Kekerasan Seksual di Perguruan Tinggi Perspektif Sosiologis - Adawiyah, Robiatul; Luayyin, Reza Hilmy; Ardli, M. Nabat (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2021)
The policy of the Minister of Education and Culture which was recently issued in the form of The Minister of Education and Culture Regulation Number 30 of 2021 raised a lot of perception and even controversy among universities and the community itself. The policy related to the increasing rise of sexual violence in the realm of Universities which has a direct or indirect impact on the optimize of the University's Tridharma which is reduced as well as quality of Higher Education which has decreased. All of policies or regulations from the government both from the president and from its ranks from the ministry are of course based on consideration of various things. However, the problems of the pros and cons of society remain unavoidable. Cases of sexual harassment or violence in the community are increasing and more and more experienced even as if endless. In this case, to find a solution it is really necessary by the government that is right and structured and without no controvertion considering the heterogeneous Indonesian society. The authors want to know how the implementation of Permendikbud Policy Number 30 of 2021 and how to understand it from a sociological view. This library research obtained from credible sources of literacy and social media. When the data accumulated, it obtained a conclusion where the power relationship described in the policy NUMBER 30 OF 2021 tends to and indicates that the power relationship is in one dimension only. While power relations in sociological theory that explains that power should built multidimentionally and covering more broadly because power in social theory explains that power is everywhere. In terms of social construction, the policy that contained in Permendikbud Ristek Number 30 of 2021 has suitable with Berger's social construction. This theory stems from a constructivist paradigm that showed social reality as a social construct created by other individual and the individual itself that determines the social world and constructed as a matter their will. Every individual has the freedom to do anything beyond the limits of his sturcture and social institutions which gives the sense that social reality occurs because it created by an individual who is free to decide everything. This is match with the policy of Permendikbud Number 30 of 2021 which understands the forms of sexual violence due to the freedom of individual in act in according to their will.